Pengaruh Social Media dan Marketplace Terhadap Minat Beli Produk Sepatu Bola - Handin Arif Rahmawati; Budi Hartono; Migunani Migunani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of social media and marketplaces on consumers' purchase intention toward online football shoes products in Indonesia. The research employed a quantitative approach with a causal descriptive design. The sampling technique used was purposive sampling, resulting in 102 respondents who had searched for or purchased football shoes through social media and marketplace platforms. Data were collected through a Google Form questionnaire and analyzed using multiple linear regression with SPSS version 25. The validity test showed that all 24 questionnaire items had correlation coefficients higher than the critical value (r > 0.361), while the reliability test indicated Cronbach’s Alpha values above 0.70, confirming that the instrument was valid and reliable. The regression equation obtained was Y = 4.614 – 0.045X₁ – 0.096X₂, with a coefficient of determination (R²) of 0.010. The partial t-test results revealed that social media (Sig. = 0.666) and marketplace (Sig. = 0.347) had no significant effect on purchase intention. Likewise, the simultaneous F-test showed that both variables did not significantly affect purchase intention (F = 0.507; Sig. = 0.604). Nevertheless, descriptive analysis indicated high mean scores for social media (4.015), marketplace (3.983), and purchase intention (4.051), suggesting that respondents held highly positive perceptions of digital marketing for football shoes products. The insignificant inferential results were likely influenced by data homogeneity and a ceiling effect, which limited the variability of respondents’ answers.